Back-analysis of a PVC geomembrane-lined pond failure. Issue 4 (August 2008) - Stark, T. D.; Newman, E. J.; Aust, R. L.
Abstract : This paper presents a case history of veneer slope failures in a non-potable water pond. The paper includes a description of slope construction and post-construction movements, field and laboratory investigations, and stability analyses used to evaluate the cause of the slides. The pond lining system was designed at a 3H : 1V slope and consists from bottom to top of native subgrade, a 0.75 mm thick poly (vinyl chloride) geomembrane, a 270 g/m 2 non-woven geotextile, and a 0.3 m thick layer of compacted soil cover over the geotextile. This paper discusses the back-analysis of the slope failures and presents recommendations for back-analyses of other slides involving geosynthetic-lined slopes.